2006
DOI: 10.1258/026835506779115807
|View full text |Cite
|
Sign up to set email alerts
|

Varisolve® polidocanol microfoam compared with surgery or sclerotherapy in the management of varicose veins in the presence of trunk vein incompetence: European randomized controlled trial

Abstract: Objective: To compare the safety and efficacy of Varisolve® 1% polidocanol microfoam sclerosant with alternative treatments for patients with varicose veins and trunk vein incompetence. Methods: An open-label, multicentre, prospective trial of 710 patients randomized to receive either Varisolve® or alternative treatment (surgery or sclerotherapy). The endpoint was ultrasound-determined occlusion of trunk vein(s) and elimination of reflux, analysed against a non-inferiority hypothesis. Results: Overall, non-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
124
2
13

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(142 citation statements)
references
References 22 publications
3
124
2
13
Order By: Relevance
“…2,5,6,[8][9][10]12,32 The nature and frequency of complications were also similar to those previously reported in the literature. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The three groups had similar improvements in the venous clinical severity score at 6 months. However, successful ablation of the great saphenous veins at 6 weeks occurred significantly less often after foam treatment (complete ablation, 55%; partial ablation with a patent segment and no reflux, 23%) than after either surgery (complete ablation, 84%; partial ablation, 6%) or laser treatment (complete ablation, 83%; partial ablation, 8%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2,5,6,[8][9][10]12,32 The nature and frequency of complications were also similar to those previously reported in the literature. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The three groups had similar improvements in the venous clinical severity score at 6 months. However, successful ablation of the great saphenous veins at 6 weeks occurred significantly less often after foam treatment (complete ablation, 55%; partial ablation with a patent segment and no reflux, 23%) than after either surgery (complete ablation, 84%; partial ablation, 6%) or laser treatment (complete ablation, 83%; partial ablation, 8%).…”
Section: Discussionmentioning
confidence: 99%
“…Observed ablation rates, in particular for foam sclerotherapy, were lower than the rates in some previous studies, which used less strict definitions of success, 1,6,10,14 but were similar to the rates reported in two randomized trials that used definitions of technical success that were similar to ours. 12,15 In contrast to the assessment of ablation in previous trials, we determined whether ablation was complete or partial on the basis of duplex ultrasound scans obtained by independent, accredited vascular technologists rather than by the surgeons who had performed the treatment. The disparity between clinical measures of success and technical success observed in this study has also been observed in other trials of treatment for varicose veins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study comparing HL/S and EVLA methods, EVLA was reported to result with less edema and blisters but no other significant differences found between (13). In comparison of foam sclerotherapy to HL/S, HL/S procedure was reported to be superior (14).…”
Section: Discussionmentioning
confidence: 95%
“…In Wright et al study [9] of 259 patients, 27% belong to C2, 46.33% to C3, 5.01% to C4, 8.88% to C5 and 12.74% to C6 and 100% with primary in etiology and pathophysiology. Superficial and deep reflux accounts for 92.66% and superficial was only 7.34%.…”
Section: Citationmentioning
confidence: 96%